Blockchain and the development of payment intermediation in Iceland : a scenario analysis - Arnar Freyr Guðmundsson 1996-; Björn Þorláksson 1995- (2020)
The aim of this study was to research what effect blockchain might have on payment intermediation in Iceland. Deep interviews were conducted with various experts inside the financial sector. Interviewees were technologically driven, holding key positions at companies within payment intermediation or associated areas. Results were presented with the application of scenario analysis. Four scenarios were staged confined by two dimensions. These dimensions were the possibility of substitute technology and industry rivalry. In the future, the potential for blockchain to influence payment intermediation in Iceland is evident. Rules and regulations are evolving, new entrants have emerged along with changes in the banking sector. The main conclusion is that payment intermediation is not considered to be a major hurdle in Iceland. Payment and interbank systems have recently been renewed. However, the Central Bank has shown interest in Central Bank Digital Currencies and new entrants might take advantage of the technology. Blockchain can be utilized in minimizing the effort of reconciliation within payments and improving the inefficient cross-border payments. As the technology still holds certain limitations, it will prove to be a cost-benefit analysis between current systems and blockchain systems.